Efektivitas Terapi Ozone terhadap Penyembuhan Luka Kaki Diabetik pada Pasien DM Tipe II - Supriadi Supriadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the effectiveness of ozone therapy in healing diabetic foot wounds in type II DM patients. The research method used is quasi-experimental with a two-group pretest control group design approach. The research instruments used were the Bates-Jensen Wound Assessment Tool (BWAT) and SOP for ozone therapy and wound care. Data were analyzed using the paired sample T-test and the independent sample T-test. The research results obtained were a bivariate analysis of the paired sample T-test in the intervention group with values ​​of t=11.945 and p=0.003 and in the control group values ​​of t= -5.705 and p=0.000. The results of the independent t-test obtained a value of t = -8.581 and p = 0.001, so it can be stated that ozone therapy is effective in healing diabetic foot wounds in type II DM patients at the Bone Woundcare Center, South Sulawesi. In conclusion, ozone therapy is effective in healing diabetic foot wounds in type II DM patients. Keywords: Diabetes Mellitus, Foot Wounds, Ozone Therapy.